Optimization of Timing and Follow-Through Principles in Animal Motion Design: A 3D Approach for the Educational Game 'Suaka Satwa' - Juyendra, Atifa Syalsabilla; Geovanne Farell; Sheanny Ocmi Sakti; Wiki Lofandri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study optimizes the principles of timing and follow-through in 3D animation for the educational game